On Generalized Topological Indices of Silicon-Carbon - Xing-Long Wang; Jia-Bao Liu; Akbar Jahanbani; Muhammad Kamran Siddiqui; Nader Jafari Rad; Roslan Hasni (Journal of Mathematics)
Let Gbe a graph with n vertices and Γu be the degree of its u-th vertex (Γx is the degree of u). In this article, we compute the generalization of Zagreb index, the generalized Zagreb index, the first and second hyper F-indices, the sum connectivity F-index, and the product connectivity F-index graphs of Si2C3−Ip,q, Si2C3−IIp,q, Si2C3−IIIp,q, and SiC3−IIIp,q.